Facile fabrication of steam-exploded poplar loaded with non-metal-doped Ni-Fe nanoparticles: Catalytic activities in 4-nitrophenol reduction and electrocatalytic reaction - Cheng Pan; Guangying Yang; Haitao Yang; Lei Wang; Jungang Jiang; Yifan Zhang; Feifan Wu (Arabian Journal of Chemistry, 2022)
A simple and effective method for preparing a non-metallic ion-doped nickel-supported catalyst is reported. Using economical and recyclable fibre raw materials as carriers, nickel-supported catalysts were prepared by adsorption and reduction at room temperature. The nanoparticles dispersed and anchored on a rational support, efficiently inhibiting their aggregation and thus enhancing the catalytic activity. For the model catalytic hydrogenation of 4-nitrophenol by NaBH4, the N-B-NiP/steam-exploded poplar (SEP) and N-B-Ni5Fe5P/SEP catalysts exhibited much better catalytic performances than the other recently reported catalysts in terms of the catalytic activity (the reaction was completed within 10 min for both aforementioned catalysts), reaction rate constant (0.19 and 0.344 min−1, respectively) and the activity factor K (19 and 34.4 min−1·g−1, respectively). The catalysts showed activities for electrocatalytic hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) under ambient conditions. In general, the reported preparation method of nickel-supported catalysts is convenient, economical and environment-friendly, and is agreement with many green chemistry and sustainable development principles; further, it employs widely available starting materials.